Uph Improvement On Production Line A Case Study - Nasir, Muhammad Amin Zaquan Mohd (Universiti Sains Malaysia, 2019)
In manufacturing industries, Lean Manufacturing is a broadly accepted philosophy. Initially, the Lean Manufacturing concept was started from the Toyota Production System (TPS). Nowadays, most of the manufacturers tend to implement lean manufacturing to improve their production and performance in order to maintain a competitive advantage in the business environment. The purpose of this paper is to study the unit per hour (UPH) improvement on the production line. This thesis focused on the improvement of UPH and the reduction of cycle time in a production line. The production line is a manual assembly line. The initial condition of the production of the product such as cycle time and takt time was collected from time study and the data was analyzed. The cycle time for a substation in each line which is Left, Remote and Right were given attention to see which station has the highest cycle time. The lean manufacturing approach helps to identify the problem in the production line and help detect the improvement opportunities in the production line. The outcome from the implementation of improvement shows the reduction of cycle time for the bottleneck station at least 37% and the output of the production able to achieve 105 units per hour.